Electrostatic instabilities as a source of picosecond termination of run- away electrons beam in high- voltage gas filled ultra- fast diode; The 19th International Toki Conference (ITC19) on Advanced Physics in Plasma and Fusion Research, Gifu, december 8-11, 2009 - Tsventoukh M. M. (2009, 2009)
В фонде НТБ ТПУ отсутствует